Antimicrobial Treatment of Asymptomatic Bacteriuria in Noncatheterized Adults: A Systematic Review. Issue 9 (7th May 2014) - Dull, Ryan B.; Friedman, Stacey K.; Risoldi, Zara M.; Rice, Eric C.; Starlin, Richard C.; Destache, Christopher J.
<x xml:space="preserve">Abstract</x> Asymptomatic bacteriuria (ASB) is a common clinical finding characterized by the presence of bacteria in the urine of an individual without signs or symptoms suggestive of urinary tract infection. Despite available guidelines on the diagnosis and management of ASB, it is often managed inappropriately. We performed a systematic review of clinical trials evaluating antimicrobial therapy for ASB, identified translational barriers to evidence‐based practice, and we offer strategies to optimize antimicrobial use for ASB. We conducted a systematic search of the PubMed, International Pharmaceutical Abstracts, Cumulative Index to Nursing and Allied Health databases, and the Cochrane Library. Randomized controlled trials, cohort trials, case‐control studies, and meta‐analyses published in the English language were included in this review if they addressed treatment of ASB with at least one antimicrobial agent in nonpregnant adults. Articles were excluded if they evaluated patients with indwelling urinary catheters or were not clinical trials. Of the 304 articles identified from the search, 287 were excluded; thus 17 articles met the inclusion criteria. Although treatment of ASB with antimicrobial therapy may improve short‐term microbiologic outcomes, the clinical significance is diminished because the effect is not sustained, there is no measurable improvement in morbidity or mortality, and some data indicate that therapy is deleterious. Several translational barriers that preclude adoption of evidence‐based practice are identified. Treatment guidelines may not achieve their desired effect and underscore the need for additional methods to translate clinical trial data into practice. Clinical pharmacists are a core member of the antimicrobial stewardship team and in an important position to participate in initiatives that promote appropriate antimicrobial use. We suggest a multifaceted approach consisting of education and frequent routine prospective audits with feedback coupled with appropriate process and outcome measures.